Penerapan Supply Chain Management Untuk Mengoptimalkan Produksi Berdasarkan Persediaan Barang - Murti Retnowo; Anita Fira Waluyo (Journal of Information System and Artificial Intelligence, 2022)
Competitive competition and the arrival of global markets are challenges, these challenges are related to getting products and services that are on time and at a low cost. Organizations or companies begin to realize this and to deal with it is not enough just to increase efficiency in organizations or companies, but the entire supply chain must be competitive. Increasing competition between companies in both local and international markets makes managers determined to focus on how to gain competitive advantage in order to stay in business. At present the achievement of fulfilling customers and getting their trust becomes more and more difficult. This can be obtained through the improvement of products and services, to fulfill both of them, one of which is the application of Supply Chain Management (SCM) and Outsourcing, SCM and Outsourcing methods have been recognized as ways to gain competitive advantage